Sepsis: a historical metamorphosis of the concepts (to the 100th anniversary of the birth of the author of the first national monograph «septic shock» Professor M. I. Lytkin) - S. A. Matveev (Журнал инфектологии)
The article presents the features of the terminology of the main concepts on the problem, of sepsis from ancient times to the present. The contribution of Professor M. I. Lytkin to the development of the doctrine of surgical sepsis as the author of isolation and justification, of its independent form — angiogenic sepsis and the first national monograph “Septic shock" is shown. The special role in further improvement of definitions of the problem, of surgical sepsis in close integration, of clinicians, morphologists, microbiologists and researchers in the field of fundamental Sciences is emphasized.